Síntese e caracterização de nanocompósitos baseados em derivados de grafeno de alta qualidade e óxido de cobalto bidimensionais - Nagaoka, Danilo Argentoni (2019)
The present work studied the possibility of synthesis of three different nanomaterials. A high-quality graphene oxide (GOHQ), a cobalt oxide in a two-dimensional structure (Co3O4-2D) and a nanocomposite between those materials. The goal was to study the capacitive properties of the synthesized materials, since the GO e o Co3O4 shows interesting perspective to be applied in different energy related areas. Thus, the search for new structures and the understanding of synthesis route are necessary. To synthesize the GOHQ we evaluate the main parameters of the modified Hummers method. And through modifications in the oxidation and reagent addition time, allied with temperature control during the process, was demonstrate the possibility to obtain a high-quality GO (GOHQ). The synthesized material showed a high structural degree (GOHQ ID/IG = 0,43 ± 0,13), yet nor reported in the literature for similar routes. The material was characterized using different techniques, the GOHQ showed significative changes in its structure, with an oxidation more likely to happen in the flake boarders, preserving the basal plane. We also demonstrated that the preservation during the oxidation propagates during the reduction, generating a high-quality reduced graphene oxide (rGOHQ). The cobalt oxide (Co3O4), is a material that has a large range of application in energy related areas. Different nanostructures of these material are well reported in literature, but its bidimensional structure (2D) it’s not very explored. Thus, we studied a hydrothermal route based in the adapted polyol method, which showed that with different solvents, surfactants and an appropriated template in a closed system (autoclave), we synthesized a cobalt oxide with structure similar to nanopetals. The Co3O4-2D was characterized through different techniques and had its electrochemical performance evaluated, showing the possibility to be applied in energy related areas. The nanocomposite was obtained with an adaptation in the polyol method. Through the change of one of the solvents for a suspension of GOHQ, was possible to synthesize the nanocomposite in a single step. The obtained Co3O4-GOHQ showed an enhanced electrochemical performance when compared with the isolated materials.